Principles of Freedom - MacSwiney, Terence J. (Terence Joseph), 1879-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Principles of Freedom" by Terence J. MacSwiney is a political treatise written in the early 20th century. The book articulates MacSwiney$1 (Bs vision for Ireland$1 (Bs freedom and independence from British rule, framing the struggle for freedom as both a moral and spiritual imperative. MacSwiney insists that true freedom goes beyond merely seeking political self-determination; it encompasses a higher philosophy of life that includes personal integrity and the unyielding pursuit of justice. At the start of "Principles of Freedom," MacSwiney outlines the philosophical underpinnings of the fight for Irish independence. He asserts that the desire for freedom originates from a spiritual necessity, emphasizing that Ireland's struggle is not solely for material benefits but for the flourishing of its character and moral integrity. MacSwiney explores themes such as the corrupting influence of tyranny, the importance of moral courage, and the inherent connection between individual virtue and national strength. He lays a foundation for understanding the broader implications of their struggle, indicating that the fight is both for the present and for generations to come, enhancing the urgency and sanctity of their cause. (This is an automatically generated summary.)s
Release date is 2004-08-07
E-text prepared by Jonathan Ingram, Martin Pettit, and Project Gutenberg Distributed Proofreaders
Keywords: Home rule -- Ireland; Irish question; Liberty